Use of feline TK1 as a biomarker in disease monitoring - Mouantri, Johan P. (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2013)
Serum thymidine kinase 1 (TK1) activity is used as a tumor marker in disease monitoring in veterinary and human medicine. TK1, an intracellular enzyme, is involved in a salvage pathway of DNA precursor synthesis. TK1 is used in DNA precursor production by catalyzing the transfer of the gamma-phosphate-group from a phosphate-donor to the 5´- hydroxyl-group of thymidine forming thymidine-monophosphate. Nucleoside monophosphosphates are finally converted into thymidine-triphosphates. TK1 activity significantly rises in the G1 and the S phase of the cell cycle. Thus, TK1 is found in dividing cells, and in the blood as an extracellular form of the enzyme. Two different TK isoforms have been identified in animal cells, one in the cytosol (TK1) and the other in mitochondria (TK2). TK1 plays a key role in cell-division, as a step in the reaction chain to introduce thymidine in to DNA. Thymidine is degraded into smaller molecules and secreted. It is found in body fluids, as a result. Due to the noticeable proliferative activity in tumor cells, TK1 enzyme activity is increased in this type of cells. Increased TK1 activity is a reflection of a high proportion of cells in S-phase of the cell-cycle. Since increased TK1 activity can be measured in serum, TK1 is a useful marker in diagnostics of neoplastic diseases. TK1 activity provides valuable information regarding disease prognosis and treatment results. Increase in TK1 levels are considered to be a sensitive and valuable marker for not only cell proliferation but also malignancy monitoring in clinical medicine. In addition, there are viruses able to induce TK production and elevated serum TK levels can be found in a variety of neoplasias as reported in clinical studies. Most of these studies concerned hematologic malignancies. E.g. TK1 is a valuable marker in non-Hodgkin's lymphoma. TK reflects clinical staging and provides noteworthy prognostic information. In both veterinary and human medicine a radioactive based test (Thymidine kinase radio-enzymatic assay: TK-REA) is commercially available to assess TK1 serum activity. For example, it is used to determine TK1 serum activity in dogs. However, TK-REA requires handling of radioactive material and costs 500 kr (€ 58) per test, which limits its use in veterinary clinical diagnostics and disease monitoring. Antibodies have been used to measure the TK1 serum concentration. Analysis of this type has been successful in canine- and human- medicine and would be valuable to evaluate in feline-medicine. Since TK1 serum has proven useful in canine- and human- medicine the hypothesis was that feline would be able to serve as a valuable biomarker in feline clinical medicine. The aim of the study was to evaluate whether feline TK1 has the potential to become a valuable biomarker in feline clinical practice. In order to evaluate TK1 as a biomarker, the enzyme’s activity in serum was measured with [3H]-dThd phosphorylation assay and with the commercially available TK-REA assay. The results were compared. The study is a first step towards better understanding the feline TK1’s role in disease diagnostics, disease monitoring, and as a proliferation biomarker in neoplastic diseases. Significant correlation was observed between the [3H]-dThd phosphorylation assay results and the commercially available TK-REA assay results. A correlation of 0.97 was found between the assay and the commercially available TK-REA measured activity. The [3H]-dThd phosphorylation assay showed a mean value of 2.04 pmol/min/mL in sera from cats with diseases, with a standard deviation of 2.07. The level of TK1 activity for healthy cats was not detectable, using a cut of value at 0.8 pmol/min/mL Both assays show a significant increase in TK activity in cats with lymphoma, leukemia and cystitis versus clinically healthy cats, signifying that TK may serve as a future diagnostic tool in clinical practice. However, the discrepancy in activity level between a cat with lymphoma and a healthy cat was not as significant as that between a dog with lymphoma and a healthy dog. In conclusion, a high TK serum activity level is greatly indicative of a hematopoietic neoplasia diagnosis, while there is a low predictability for cats with low TK serum activity level. The findings show that feline TK1 has the potential to become a valuable biomarker in clinical practice. These finding in combination with the overview of the lymphoma diagnostic challenges indicate that TK1 has the potential to become a valuable biomarker in clinical practice.